Ceria Nanoparticles Shape Effects on the Structural Defects and Surface Chemistry: Implications in CO oxidation by CuO/CeO2 oxides - Sónia A. C. Carabineiro (2018)
Copper-ceria binary oxides have been extensively used in a wide variety of catalytic processes due to their unique catalytic features in conjunction to their lower cost as compared to noble metal-based systems. However, various parameters related to different counterparts characteristics, such as particle size and morphology, can exert a profound influence on the structural/redox properties of binary oxides and, consequently, on their catalytic performance. Here, we report on ceria nanoparticles shape effects: nanorods (NR), nanopolyhedra (NP) and nanocubes (NC) on the solid state properties of copper-ceria binary oxides. A thorough characterization study by both ex situ (surface area determination, X-ray diffraction, X-ray fluorescence, H2-temperature programmed reduction, transmission electron microscopy, X-ray photoelectron spectroscopy) and in situ (Raman spectroscopy) techniques was undertaken to gain insight into the impact of the support morphology on the surface, structural and redox properties. A novel approach based on sequential in situ Raman spectra obtained under alternating oxidizing and reducing atmospheres was employed to reveal the impact of ceria exposed facets on the structural defects. CO oxidation was employed as a probe reaction to disclose structure-property relationships. The results clearly revealed the key role of ceria morphology rather than structural/textural characteristics on the reducibility and oxygen mobility, following the sequence: NR > NP > NC. The latter seems to have a profound influence on copper-ceria interactions towards the stabilization of Cu+ species, via Ce4+/Ce3+ and Cu2+/Cu+ redox equilibrium. Interestingly, CuO incorporation in different ceria carriers boosts the catalytic activity without, however, affecting the order observed for bare ceria, i.e., CeO2-NR > CeO2-NP > CeO2-NC, implying the key role of support. The Cu/CeO2 sample with the rod-like morphology exhibited the highest catalytic performance, offering almost complete CO elimination at temperatures as low as 100 °C. A perfect relationship between the catalytic performance and the following parameters was disclosed, on the basis of a Mars-van Krevelen mechanism: i) abundance of weakly bound oxygen species, ii) relative population of Cu+/ Ce3+ redox pairs, iii) relative abundance of defects and oxygen vacancies.